The Cosmopolitics of Resistance: The Belo Monte Dam and the Struggle of Riverine Communities - Chaves, Kena Azevedo [UNESP]; Weiβermel, Sören (Taylor & Francis, 2023)
The Belo Monte Hydroelectric Plant in the Brazilian Amazon caused an 80% reduction in the flow of the Xingu River downstream of the main dam. Affected riverine people claim losses and the precarization of living conditions and are engaged in a dispute over water and the permanence of their territories. Based on documentary research, observations, and dialogues with riverine people, we highlight the cosmopolitical dimension of resistance to dispossession, which involves human and non-human agency. From this perspective, the struggle for recognition as a traditional people is not only a strategy for defending rights but a way to politicize the nonhierarchical, intertwined relationship between the riverines and nature. We argue that the cosmopolitical perspective captures the onto-epistemic dimension, which is crucial in both dispossession and people’s resistance. Such conflicts highlight violent dimensions of dispossession and, at the same time, make visible the politicization of the relationship between humans and non-humans.
Keywords: Accumulation by dispossession; Brazilian Amazon; cosmopolitics; epistemologies; human-environment relationship; ontologies; riverine people